When personal experience overlaps with study. (2nd June 2021) - Osborne, Emma; Robson, Bridget; Anderson, Vivienne
Abstract: Background: Health professional education programmes increasingly seek to train a generation of clinicians who reflect the population they serve. However, teaching approaches in health professional education have not always kept pace with this drive, and some educators tend to assume a lack of overlap between students' life experience and aspects of the curriculum. Method: In‐depth interviews were conducted with 22 health professional students and graduates, who self‐identified as having experienced a significant overlap between their personal life and their course of study. These interviews were analysed thematically to explore the role of teaching practices that created either alienating or inclusive learning environments. Results: Participants identified areas where clinical teachers could modify their teaching approach and assumptions about the student cohort to be more inclusive of students whose life experience overlapped with the curriculum. They wanted educators to treat any teaching topic as if it could be personal for some students, which may include teaching inequities carefully, acknowledging family members' perspectives, moderating discussions, and avoiding stereotyping patients. Participants also wanted educators to practice shared decision‐making about alternative arrangements or time off. Discussion: Clinical educators have a key role in shaping an inclusive health sciences programme. Their assumptions, attitudes and teaching strategies can either strengthen or undermine the development of a diverse health workforce.